Treasury Single Account System and Utilization of Internally Generated Revenue in University of Ilorin, Kwara State, Nigeria - OMOSIDI, Abdulrahman Suyuti; ATOLAGBE, Adedapo. Adetiba; OLADIPUPO, Musa. Yekini (Journal of Arts & Social Sciences, 2020)
This study investigated the impact of TSA on revenue generation and utilization in the University of Ilorin. Since the implementation of Treasury Single Account (TSA) in 2015 by the present administration in government with the intention to control financial mismanagement which will consequently improve government revenue and economic growth; stakeholders, researchers, and the general public are interested to know the extent to which these objectives have been met. This study empirically examined the extent to which TSA has an effect on total revenue (Grant+IGR) and its utilization. Both the interview and secondary data were utilized for this study. The interview session was for the staff of the Bursary Department of the University. Total fund allocated (Grant+IGR) and its utilization at the University of Ilorin for the period 2012 – 2017 was collected from the Unilorin Annual Reports. The data were divided into two periods: Pre TSA period (2012 to 2014) and Post TSA period (2015 to 2017). A pre-post analysis (difference in means test) was carried out using SPSS version 20. Findings show that the implementation of the Treasury Single Account has improved revenue generation in the University. However, further findings revealed that University’s revenue utilization improved after the implementation of TSA from N6, 691,451,094.41 billion to N8, 928,707,239.14 billion. It was recommended that university administrators, should, as a matter of importance, device other means of boosting their internally generated revenue. This should, however, be done within the ambit of the law.